Influence of technological dose of irradiation on mechanical and electrical characteristics of polymeric insulation of wires - Bezprozvannych, G. V.; Mirchuk, I. A. (Національний научний центр "Харківський фізико-технічний інститут", 2018)
Creation of cables and wires with polymer insulation without halogens based on ethylene vinyl acetate with a high content of fire retardants is impossible without radiation modification properties. On the industrial accelerator of charged particles, the effect of ionizing radiation on wires with a copper conductor cross section of 1.0 mm2 and an insulation thickness of 0.7 mm is performed. The influence of the electron energy at identical irradiation factors on the increase in the mechanical strength of insulation during stretching is shown. For electron energy of 0.5 MeV, an increase in the mechanical strength of insulation at a tension of 27% was established, the insulation resistance more than doubled, and the breakdown voltage by 35% at the optimum radiation dose relative to the unirradiated state.

Створення кабелів і проводів з полімерною ізоляцією без вмісту галогенів на основі сополімеру етиленвінілацетату з високим вмістом антипіренів неможливо без радіаційного модифікування властивостей. На промисловому прискорювачі заряджених частинок виконано вплив іонізуючого випромінювання на зразки проводу з мідною жилою перетином 1,0 мм2 і товщиною ізоляції 0,7 мм. Показано вплив енергії електронів при однакових коефіцієнтах опромінення на підвищення механічної міцності ізоляції при розтягуванні. Для енергії електронів 0,5 МеВ встановлено підвищення механічної міцності ізоляції при розтягуванні - на 27%, опору ізоляції – більш ніж в два рази і пробивної напруги – на 35% при оптимальній дозі опромінення щодо неопроміненого стану
Влияние технологической дозы облучения на механические и электрические характеристики полимерной изоляции проводов
Вплив технологічної дози опромінення на механічні і електричні характеристики полімерної ізоляції проводів
Keywords: cables; polymer insulation; ethylene vinyl acetate; radiation modification properties; ionizing radiation; mechanical strength of insulation